Prekindergarten and Kindergarten Center-based Child Care and Students' Early Schooling Outcomes. Issue 11 (November 2015) - Gottfried, Michael A.
Background/Context: In the United States, there has been an increased trend in parents' utilization of center-based child care. Yet, though research has examined the effects of attending prekindergarten center-based care or the effects of attending center-based care during the kindergarten school year, little is known about the effects of having attended both. Purpose/Objective: This study asks three questions: (a) Do children who attend both prekin-dergarten and kindergarten center-based care have different achievement outcomes, measured at the end of kindergarten? (b) Do children who attend both prekindergarten and kindergarten center-based care have different socioemotional outcomes, measured at the end of kindergarten? (c) Do these relationships differ by individual socio-demographic characteristics? Population/Participants: This study utilizes data from the newly released Early Childhood Longitudinal Study – Kindergarten Class of 2011 (ECLS-K:2011). The ECLS-K:2011 represents the most contemporary national-level data available to study the educational experiences of young students in the United States. Information was first collected from kindergartners (as well as parents, teachers, and school administrators) from U.S. kindergarten programs in the year 2010–2011. Research Design: This study combines secondary data analyses and quasi-experimental methods. There are two achievement outcomes: reading and math. There are five socioemotional outcomes: externalizing behaviors, internalizing behaviors, self-control, approaches to learning, and interpersonal skills. The study begins with a baseline, linear regression model. To address issues pertaining to omitted variable bias, the study employs various fixed-effects models. Findings: The findings for the first research question indicated that academic outcomes do not differ for children in both years of center-based care compared to children who attended only one year of center-based care or none at all. As for the second research question, the findings show that multiple years of center-based care is related to increases in problem behaviors and decreases in prosocial behaviors—outcomes that are worsened by the number of years of center-based care attendance. The findings for the third research question suggest some minor differences between boys and girls in zero, one, or two years of center-based care. Conclusions/Recommendations: This study has brought to surface new ways that center-based care attendance might influence children's short-term outcomes. Therefore, researchers, policymakers, and practitioners must base future questions on empirical work concerning how to address children's outcomes across multiple years of care, rather than simply focus exclusively on one year's influence.